Active forms of tourism among lower and higher secondary students in Cracow - Jurczak, Adam; Żiżka-Salamon, Danuta (Geotourism/Geoturystyka, 2014)
The purpose of this paper is to determine organizational forms (formal, non-formal) and the level of tourism activity among young people of secondary schools in Cracow depending on gender, the type of school and the education of the parents. The study included 1472 students of schools in Cracow. Physically active forms of tourism are undertaken mostly by girls – 63% rather than by boys – 52%. With increasing levels of education of the parents, the number of young people practicing active forms of tourism also increases. The undertaking of active forms of tourism varies, depending of the type of school attended. Young people in secondary (63,9%) and primary (65,7%) schools most often chose to go for tourism. In primary (50,1%) and secondary (39,4%) vocational schools they go least often. Active forms of tourism usually take the form of informal practice among friends and acquaintances (mostly hiking – 47%).